Design and operation of on-farm storage facilities for demand oriented irrigation scheme - Mehta, Brijesh Kumar; Goto, Akira; Murty, V.V.N.; Paudyal, Guna N.; Government of Japan (Bangkok : Asian Institute of Technology, 1990)
In irrigation systems, water demand usually shows large fluctuations due to rain, crop growth, non-availability of labor etc., which water supply can not follow. It may lead to over- and under- irrigation and result in low water use efficiency, Hence irrigation system should be designed to satisfy fluctuating water demand and at the same time prevent invalid overflow. On-farm storage facilities are expected to be useful for this purpose. In this study irrigation system is assumed to consist of an intermediate reservoir (regulating reservoir, IR) and a chain of internal water storage facilities (farm ponds, FP). The purpose of a farm pond is to smoothen daily fluctuations whereas an intermediate reservoir balances seasonal fluctuations of irrigation water demand. The FP model was developed for determination of storage capacity and operation rule of a farm pond, at various conditions such as cropping pattern, area of command, hourly irrigation demand, and at various reliability levels. For operation of farm pond four operating rules were formulated and out of them best one was selected for the present study. The IR model was also developed for determination of storage capacity of intermediate reservoir at various reliability levels. These FP and IR models were applied to Mae-Taeng Irrigation Project in Chiang Mai Province, Thailand. The storage capacities of farm ponds and intermediate reservoir were determined under various cropping patterns, hourly demand patterns, for various reliability levels. It was confirmed that both farm pond and intermediate reservoir can increase water use efficiency and decrease deficit. It was also observed that a good operating rule can give less required storage capacity. It was found that storage capacity of farm pond is governed by both wet and dry season crops. For various parameters of ARMA model for generation of water demand, about 5 to 10% variation in the storage capacity was observed. However 10 to 20% variation in storage capacity was observed due to hourly demand variatio
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1990
Keywords: Water-storage -- Design and construction